Revised CHARMM force field parameters for iron‐containing cofactors of photosystem II. Issue 1 (28th August 2017) - Adam, Suliman; Knapp‐Mohammady, Michaela; Yi, Jun; Bondar, Ana‐Nicoleta
Abstract : Photosystem II is a complex protein–cofactor machinery that splits water molecules into molecular oxygen, protons, and electrons. All‐atom molecular dynamics simulations have the potential to contribute to our general understanding of how photosystem II works. To perform reliable all‐atom simulations, we need accurate force field parameters for the cofactor molecules. We present here CHARMM bonded and non‐bonded parameters for the iron‐containing cofactors of photosystem II that include a six‐coordinated heme moiety coordinated by two histidine groups, and a non‐heme iron complex coordinated by bicarbonate and four histidines. The force field parameters presented here give water interaction energies and geometries in good agreement with the quantum mechanical target data. © 2017 Wiley Periodicals, Inc. Abstract : Photosystem II uses the energy of absorbed light and cofactor molecules to catalyze the splitting of water molecules into molecular oxygen, protons and electrons. To facilitate reliable all‐atom computations of photosystem II, CHARMM force field parameters was derived for the two iron‐containing cofactors of the complex. Simulations of neuroglobin demonstrate that parameters presented here allow accurate description of the bis‐histidine‐coordinated heme moiety.